The Correlation Between Students' Public Speaking Ability & Their Communication Strategy at STKIP Abdi Pendidikan Payakumbuh - Zahra Suamperi, Siti Fakhirah; Ratmanida, Ratmanida (Universitas Negeri Padang, 2024)
Some students encountered difficulties in the context of Public Speaking, necessitating the formulation of a strategic approach. Consequently, the researcher aims to investigate the relationship between the public speaking proficiency of students and their communication tactics within the Public Speaking Course at STKIP Abdi Pendidikan Payakumbuh. This particular study adopted a correlational research design, with the target population were English Education students in their 4th semester at STKIP. Class A and Class B were selected as the sample through total sampling method. The research utilized the Public Speaking Test and CS Questionnaire as data collection instruments, and the gathered data underwent analysis using SPSS 25 for Windows. The statistical analysis employed the Pearson Correlation test. The results indicated that with a significance value of 0.000<0.05, the alternative hypothesis was upheld, suggesting a correlation between public speaking ability and communication strategy. Moreover, the students exhibited a good level of public speaking ability, with stalling emerging as the dominant communication strategy utilized by the students.